Responses of the Black Fungus Cryomyces antarcticus to Simulated Mars and Space Conditions on Rock Analogues - Pacelli, C.; Selbmann, L.; Zucconi, L.; Coleine, C.; de Vera, J.-P.; Rabbow, Elke; Böttger, Ute; Dadachova, E.; Onofri, S. (Astrobiology, 2019)
The BIOMEX (BIOlogy and Mars Experiment) is part of the European Space Agency (ESA) space Mission EXPOSE-R2 in Low-Earth Orbit, devoted to exposing microorganisms for 1.5 years to space and simulated Mars conditions on the International Space Station. In preparing this mission, dried colonies of the Antarctic cryptoendolithic black fungus Cryomyces antarcticus CCFEE 515, grown on martian and lunar analog regolith pellets, were subjected to several ground-based preflight tests, Experiment Verification Tests, and Science Verification Tests (SVTs) that were performed to verify (i) the resistance of our model organism to space stressors when grown on extraterrestrial rock analogues and (ii) the possibility of detecting biomolecules as potential biosignatures. Here, the results of the SVTs, the last set of experiments, which were performed in ultraviolet radiation combined with simulated space vacuum or simulated martian conditions, are reported. The results demonstrate that C. antarcticus was able to tolerate the conditions of the SVT experiment, regardless of the substratum in which it was grown. DNA maintained high integrity after treatments and was confirmed as a possible biosignature; melanin, which was chosen to be a target for biosignature detection, was unambiguously detected by Raman spectroscopy.